Teaching academic writing: A shift towards intercultural rhetoric - Elina S. Chuikova (Peoples' Friendship University of Russia (RUDN University), 2020)
New trends in cross-cultural studies are aimed at the analysis and definition of interculture that is generated in a classroom in the process of cultural integration. Academic writing interculture remains a potentially appealing area for research since this topical issue is almost neglected in the Russian-English interactive teaching context. Sociocultural peculiarities of the English and Russian rhetorical traditions have been thoroughly investigated by the English-speaking and native scholars. However, the characteristics of a new culture formed by the merging of different traditions are under discussion. Intercultural rhetoric brings a new and expended view on writing culture and requires further research. The paper presents statics on the basis of Master's students' texts, estimates which elements of academic writing merge. The author studies various levels of cultural mismatches, discusses if the integration tendencies take place at any of text creation levels, and argues that authenticity coupled with individuality pertains greatly to the quality of academic texts. In conclusion the tendencies and changes in academic writing style and individual thinking style of the Russian students are summarised. The results indicate the formation of two major characteristics in academic intercultural communication: individuality and authenticity.